Kepatuhan Masyarakat Dalam Melakukan PHBS Rumah Tangga Di Wilayah Kerja Puskesmas Pandere Kecamatan Gumbasa Kabupate Sigi - Sri Purwiningsih; Anggri Alfira Yunita Assa; Mutmainnah HS; Robby Adikari Sekeon (CV. Multi Kreasi Media, 2026)
In general, the public still considers clean and healthy living (PHBS) a personal matter that is not particularly important for health. Some people still lack toilets at home or defecate in the open. Based on observations conducted by researchers in three households in the Pandere Community Health Center (Puskesmas) area, two households used smelly water for cooking and washing, three households did not cover water reservoirs, and one household did not have a toilet. The purpose of this study was to determine community compliance with Clean and Healthy Living Behaviors (PHBS) in households within the Pandere Community Health Center area, Gumbasa District, Sigi Regency. This study was descriptive. The variable in the study was household compliance with PHBS. Primary and secondary data were used. Data were analyzed using univariate analysis. The population in this study was all heads of families in the Pandere Community Health Center area, totaling 5,132 people. A sample size of 44 people was selected. The results showed that of the 44 respondents, 54.6% were more compliant with implementing Clean and Healthy Living Behaviors (PHBS) at home, compared to 45.4% who were less compliant. The conclusion of this study is that the majority (54.6%) of the community in the Pandere Community Health Center's work area is compliant with implementing Clean and Healthy Living Behaviors (PHBS) at home. The Pandere Community Health Center recommends that they continue to provide PHBS education to the community to increase their compliance with PHBS at home.